A qualitative evaluation of a physician-delivered pedometer-based step count prescription strategy with insight from participants and treating physicians. (May 2018) - Cooke, Alexandra B.; Pace, Romina; Chan, Deborah; Rosenberg, Ellen; Dasgupta, Kaberi; Daskalopoulou, Stella S.
Highlights: This study explored physician and patient views of a step count prescription strategy. Step increases were facilitated by target setting and accountability of the strategy. Barriers included poor weather, health limitations and work constraints. The strategy was easily integrated into the patient-physician encounter. Support from the health care team may be needed to help deliver the strategy. Abstract: Aims: The integration of pedometers into clinical practice has the potential to enhance physical activity levels in patients with chronic disease. Our SMARTER randomized controlled trial demonstrated that a physician-delivered step count prescription strategy has measurable effects on daily steps, glycemic control, and insulin resistance in patients with type 2 diabetes and/or hypertension. In this study, we aimed to understand perceived barriers and facilitators influencing successful uptake and sustainability of the strategy, from patient and physician perspectives. Methods: Qualitative in-depth interviews were conducted in a purposive sample of physicians (n = 10) and participants (n = 20), including successful and less successful cases in terms of pedometer-assessed step count improvements. Themes that achieved saturation in either group through thematic analysis are presented. Results: All participants appreciated the pedometer-based monitoring combined with step count prescriptions. Accountability to physicians and support offered by the trial coordinator influenced participant motivation. Those who increased step counts adopted strategies to integrate more steps into their routines and were able to overcome weather-related barriers by finding indoor alternative options to outdoor steps. Those who decreased step counts reported difficulty in overcoming weather-related challenges, health limitations and work constraints. Physicians indicated the strategy provided a framework for discussing physical activity and motivating patients, but emphasized the need for support from allied professionals to help deliver the strategy in busy clinical settings. Conclusion: A physician-delivered step count prescription strategy was feasibly integrated into clinical practice and successful in engaging most patients; however, continual support is needed for maximal engagement and sustained use.